'Europe is finished': migrants lives in Europe's capital at times of crisis. (4th March 2019) - Loftsdóttir, Kristín
ABSTRACT: Migration has become a key issue in the contemporary European context, with depictions of Europe as under 'attack' due to the mass movement of uprooted populations, especially from Africa and the Middle East. The current sentiment of Europe in crisis calls for a deeper understanding of how the idea of Europe is configured. This article focuses on the idea of 'Europe' as seen from the point of view of Nigerien men who are living in Brussels without residency permits. Their voices reveal some of the gaps in contemporary discourses concerning crises and Europe's predicament, especially in terms of terror and refugees. Their narratives point to how current debates on migration and crisis tend to rely on an image of a disconnected world, which obfuscate Europe's historical interconnections with those now seeking entrance into Europe. Muslim migrants, in particular, are regularly portrayed as being incompatible with modernity, reflecting the persistent refusal to acknowledge their coevalness in Fabian's [2014. Time and the other: How anthropology makes its object . New York: Columbia University Press] sense, that is to say their coexistence in the same time and space. One aspect of shared coexistence is 'digitalized connectivity' where media representations of Europe in crisis are an integral part of the lives of these migrant men as others living in Europe.